Managing Early Literacy Learning in Grade One Elementary Classrooms - Eka Syafitri; Dessy Wardiah; Syaiful Eddy (Journal of Social Work and Science Education, 2027)
Early literacy in the first grade is not only a technical matter of teaching children to identify letters, syllables, and simple words; it is also a managerial issue that requires planning, classroom organization, instructional enactment, assessment, and family-school coordination. This study describes how early literacy learning was managed in a Grade One classroom at an Indonesian public elementary school, identifies supporting and inhibiting factors, and formulates practical improvements for sustained literacy development. A qualitative case study was conducted at SD Negeri 96 Palembang. Data were collected through classroom observation, semi-structured interviews with one Grade One teacher, the principal, the school literacy coordinator, and three parents, and documentation of lesson modules, reading corners, assessment notes, and school literacy records. The data were analyzed thematically through reduction, display, verification, and triangulation across methods and sources. The findings show that early literacy management operated through coordinated planning, Merdeka Curriculum-based lesson modules, 10-15 minute daily reading routines, read-aloud, shared reading, guided reading, local folklore texts, ability-based grouping, reading corners, daily formative assessment, portfolios, and semester reflection. The novelty of this study lies in positioning early literacy as an integrated classroom-management and school-management practice rather than a single reading activity. The study contributes a practical model for strengthening early literacy through differentiated instruction, locally contextual materials, common teaching guidelines, and structured parental involvement.